A Conceptual Framework for Resilience and Sustainability Development in Displaced Rural Communities: Addressing Socio-Economic Challenges in Sungai Asap, Sarawak - Yee Ong, Sharon Yong; Teruki, Neilson; Taasim, Shairil Izwan; Yaccob, Yasmin; Radzlan, Rohaizahtulamni (HRMARS, 2024)
Sungai Asap, located in the Belaga district of Sarawak, Malaysia, was established in 1998 to resettle communities displaced by the Bakun Dam, Southeast Asia's largest hydroelectric project. Predominantly home to Kayan, Kenyah, Penan, and Ukit ethnic groups, the community has encountered profound socio-economic transformations linked to forced relocation, infrastructure development, and large-scale modernization efforts. This paper presents a conceptual framework to analyze the socio-economic challenges faced by Sungai Asap, situating these within broader discussions of rural displacement, resilience, and sustainable development. This study explores the socio-economic impacts of displacement, focusing on poverty, unemployment, limited educational access, and infrastructural constraints that hinder sustainable development in Sungai Asap. Additionally, it examines the social and cultural disruptions stemming from relocation, with a particular focus on how developmental imbalances may compound these issues and affect quality of life. By synthesizing these factors within a conceptual framework, this paper seeks to advance understanding of the intersecting challenges faced by displaced rural communities in the context of large-scale development projects. Through this framework, the study generates strategic recommendations for enhancing resilience and sustainability, emphasizing the role of inclusive development and culturally sensitive policies. This conceptual paper also aims to serve as a reference point for further research, proposing new pathways for socio-economic stability and quality of life improvements in rural resettlement contexts.